Solar Energy Zeolite Regeneration for a Milk Cooler - Bariho, Davis; Kisaalita, William S.; Kasisira, Levi (Tarım Makinaları Bilimi Dergisi, 2008)
Despite the rehabilitation of Uganda’s milk infrastructure, almost 50% of the milk collected by small holder farmers is wasted due to inability to store the milk and the unsafe conditions of transporting it to collection centers. To alleviate this problem, a zeolite adsorption cooler can be used but once it is fully saturated, it must be regenerated. Conventional processes of regenerating it by electrical heating have high levels of energy consumption and are not cost friendly to the rural farmers. The objective of this study therefore was to investigate the use of solar energy in regenerating the zeolite adsorbent. In this study, solar energy regeneration of three zeolite sizes as 1/2x1/4, 4x8 and 6x14 was investigated on convective aluminum pan dryers in open solar drying. Experiments were conducted for Bear river zeolite. The constant rate period was absent from the drying curves with zeolite 6x14 size showing the fastest drying rate and recorded the highest efficiency. Moisture ratio at any drying time was compared by 14 mathematical models using the correlation coefficient (R), root mean square error (RMSE) and chi-square (2) parameters. Modeling efficiency was determined for each model. The effect of drying air temperature, relative humidity and velocity on the coefficients of the best suited model was determined by multiple regression analysis. According to the results, Modified page I model best explained the open sun drying behavior of Zeolite. Moisture content of the material can be predicted more easily with the generalized model showing the effect of drying air temperature, relative humidity and velocity on the model constants and coefficients